2020
DOI: 10.3389/fnmol.2020.560891
|View full text |Cite
|
Sign up to set email alerts
|

Hepcidin Decreases Rotenone-Induced α-Synuclein Accumulation via Autophagy in SH-SY5Y Cells

Abstract: Parkinson's disease (PD) is a neurodegenerative disorder, and the hallmarks of this disease include iron deposition and α-synuclein (α-syn) aggregation. Hepcidin could reduce iron in the central and peripheral nervous systems. Here, we hypothesized that hepcidin could further decrease α-syn accumulation via reducing iron. Therefore, rotenone or α-syn was introduced into human neuroblastoma SH-SY5Y cells to imitate the pathological progress of PD in vitro. This study investigated the clearance effects of hepcid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 48 publications
(53 reference statements)
2
10
0
Order By: Relevance
“…Our result showed that ROT led to a significantly upregulated α-syn level by 239% compared to the control group, which agrees with ( Li et al, 2020 ) and significantly down-regulated parkin protein by 67%, which is compatible with ( Rahimmi et al,2015 ), while EMP + ROT resulted in significant preservation in these protein levels. α-syn is a fundamental contributor in PD, which can initiate and potentiates the neurodegeneration process by many pathways; inhibition of autophagy, induction of mitochondrial dysfunction, and increased oxidative stress in addition to microglial activation causing neuroinflammation and an increase in proinflammatory cytokines ( Segura-Aguilar, 2017 ).…”
Section: Discussionsupporting
confidence: 83%
“…Our result showed that ROT led to a significantly upregulated α-syn level by 239% compared to the control group, which agrees with ( Li et al, 2020 ) and significantly down-regulated parkin protein by 67%, which is compatible with ( Rahimmi et al,2015 ), while EMP + ROT resulted in significant preservation in these protein levels. α-syn is a fundamental contributor in PD, which can initiate and potentiates the neurodegeneration process by many pathways; inhibition of autophagy, induction of mitochondrial dysfunction, and increased oxidative stress in addition to microglial activation causing neuroinflammation and an increase in proinflammatory cytokines ( Segura-Aguilar, 2017 ).…”
Section: Discussionsupporting
confidence: 83%
“…Even though our studies examining rotenone-induced toxicity have employed short-term and relatively high levels of rotenone exposure, over a lifetime, the patients may have been exposed to the toxins for several years at relatively low concentrations. 104 Summing up, the results of these assays confirm the neuroprotective properties of the tested compounds 13−15, predominantly via inhibition of ROS production and the significantly lower effect on the metabolic activity of SH-SY5Y cells. The β-naphthyl dimethyl-branched derivative 15 turned out to be the relatively most potent neuroprotective agent in these studies.…”
Section: ■ Results and Discussionsupporting
confidence: 54%
“…It is worth noting that the concentration of rotenone in this study was adjusted based on a dose–response curve of rotenone, in which a significant increase in ROS level and decrease in metabolic activity of SH-SY5Y cells in vitro were observed. Even though our studies examining rotenone-induced toxicity have employed short-term and relatively high levels of rotenone exposure, over a lifetime, the patients may have been exposed to the toxins for several years at relatively low concentrations …”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, cells treated with TCN, an AKT inhibitor, showed that the phosphorylation of GSK-3β in EGF treated PC3 cells was reduced [106]. Studies have shown that rotenone, a pesticide associated with α-synuclein aggregation, induces intercellular calcium levels and suppresses AKT and GSK-3β phosphorylation [104,108]. In this study, they showed that BAPTA, a chelator of intracellular calcium, can alleviate the downregulation of AKT and GSK-3β phosphorylation induced by rotenone treatment [104].…”
Section: Calcium Regulates the Activation Of Gsk-3βmentioning
confidence: 58%